The Penerapan Model Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar Siswa Kelas XI dalam Pembelajaran Nail Art Wedding di SMK Labschool UNESA 1 Surabaya: Penerapan Model Pembelajaran Berbasis Proyek - Shindy Shindy Puspitasari; Dindy Sinta Megasari; Sri Usodoningtyas; Octaverina Kecvara Pritasari (Program Studi Pendidikan Tata Rias, 2026)
This study aimed to determine the implementation of the Project Based Learning (PjBL) syntax, students' learning outcomes in the cognitive, affective, and psychomotor domains, and students' responses to the implementation of the Project Based Learning (PjBL) model in Wedding Nail Art learning at SMK Labschool UNESA 1 Surabaya. This study employed a descriptive quantitative research method using a Pre-Experimental Design with a One-Shot Case Study design. The research subjects consisted of 33 Grade XI students of the Beauty and Hair Care Program (TKKR) at SMK Labschool UNESA 1 Surabaya. Data were collected through observation, tests, and student response questionnaires. The data were analyzed descriptively using quantitative methods based on mean scores and percentages. The results showed that the implementation of the PjBL syntax achieved an average score of 91.7, categorized as excellent. Students' learning outcomes in the cognitive domain obtained an average score of 86.5 (good category), the affective domain achieved 87.2 (good category), and the psychomotor domain reached 88.5 (excellent category). Students' responses to the implementation of the PjBL model obtained a percentage of 90.3%, categorized as excellent. Based on these findings, it can be concluded that the implementation of the Project Based Learning (PjBL) model in Wedding Nail Art learning was effective in improving the quality of the learning process, enhancing students' learning outcomes, and generating positive responses from students. Therefore, this learning model is appropriate to be used as an innovative instructional alternative in vocational education, particularly in the field of beauty education. Keywords: Project Based Learning, PjBL syntax, Wedding Nail Art, learning outcomes, student responses.